Modernisasi Masjid: Analisis Tindakan Sosial Pemasangan Wifi pada Masjid Di Kota Kediri - Alif Hasugian (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This research aims to discuss the social action of installation on mosques in Kediri City. This research is a type of qualitative research with a phenomenological approach, namely by describing in detail the social actions of wifi installation. Furthermore, this study will adopt Max Weber's theory of social action as a knife of analysis in determining the form of social action carried out by mosque administrators. The results of this study show that social actions carried out by mosque administrators are a form of rationality of values. The motives of each mosque administrator are different but with the same purpose, namely in order to meet the needs of the community and make the mosque. The study recommends academics and research to further develop the theme of this research but with a different approach, so as to contribute to socio-religious research in a sustainable manner.